ВЛИЯНИЕ СОВРЕМЕННЫХ ТЕХНОЛОГИЙ НА СНИЖЕНИЕ КОГНИТИВНОГО СТАТУСА МОЛОДЁЖИ КАК ФАКТОР РИСКА ПОПАДАНИЯ В ПСЕВДОНАУЧНЫЕ ОККУЛЬТНЫЕ ОРГАНИЗАЦИИ - Айрапетова, А.Г. (SCIENCE and SOCIETY, 2017)
Influence of modern information-communication technologies on cognitive status of youth was considered in the article. Influence of multitasking, as information overloading, on perceptions, attention, memory and thinking parameters reduction was demonstrated. Interrelation of reduced cognitive status with possibility of involvement in pseudoscientific occult organizations was presented. Some methods of recruitment to sects were exposed.